MEMBANGUN EKONOMI SYARIAH MELALUI NILAI EKOLOGI DAN MODERASI BERAGAMA: SEBUAH PENDEKATAN MAQASHID SYARIAH - Sumar'in (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to construct a model of just Islamic economics through the integration of ecological values and religious moderation based on the framework of maqashid al-sharia. The research is motivated by the urgent need to develop an Islamic economic paradigm that is not only growth-oriented but also emphasizes sustainability and universal well-being. Theoretically, this study employs a qualitative-descriptive approach with a normative analysis of relevant literature on fiqh al-bi’ah (Islamic environmental jurisprudence), maqashid al-sharia, and religious moderation. The findings reveal that maqashid al-sharia serves as the normative foundation guiding the direction and objectives of Islamic economics; ecological values act as the pillar of sustainability, ensuring harmony between economic activity and environmental preservation; while religious moderation provides the ethical framework to guarantee that economic practices remain just, balanced, and free from extremities. The integration of these three components produces a humanistic and ecological Islamic economic model, in which maslahah (public good) is understood not only as human welfare but also as the cosmic balance encompassing all of God’s creation. This study highlights the necessity for Islamic economics to evolve beyond a merely halal financial system toward a morally grounded, socially just, and ecologically sustainable economic paradigm